Diseño de un sistema de gestión de inocuidad, basado en la norma ISO 22000:2005 en una planta de cárnicos en Quito - Reyes Cueva, Jenny Gabriela (2018)
The present work has been carried out in a meat processing plant in Quito- Ecuador, which is certified in Good Manufacturing Practices (GMP), and implemented with Hazard Analysis and Critical Control Points (HACCP), to have this system of management allowed it to be a provider of a chain of restaurants under the guidelines of the YUM standard, in the last three years it has had an increasing demand for product with an average growth of ten percent month to month, have a Management System ISO 22000, combine Pre requisite program, operational Pre requisite program and Critical Control Points analysis. The company in its continuous improvement seeks to satisfy the needs of its customers and capture new opportunities in the market, so it is essential to have a robust Management System, so first-hand a diagnosis was made by applying a checklist based on the ISO 22000: 2005 standard in which the following results were obtained: for Section 4. Food Safety Management System a 72,58 percent was obtained, for Section 5. Management Responsibility a 63,5 percent, for Section 6. Resource Management a 72,06 percent, for Section 7. Planning and realization of Safe Products an 89,95 percent, finally for Section 8. Validation, verification and improvement of the food safety management system a 74,19 percent. On average, 74,5 percent of total compliance with the standard was obtained, identifying opportunities for improvement in documentary updating; of the procedures already lifted, readjustment in the profile of positions, follow-up with the meetings of the safety team, investment in the meat processing plant with infrastructure, machinery, labor and communication. A set of indicators of effectiveness was raised, related to customer satisfaction and efficiency according to product returns, cleaning and disinfection procedures, personnel training, industrial safety and environment aligned with objectives Smart according to the safety and quality policy of the meat processing plant.